Blood block: una aplicación basada en blockchain para el soporte de hemovigilancia en los servicios transfusionales (2020)
In Colombia it has been estimated, according to the National Institute of Health, that at least 20% of transfusions present some kind of long-term or short-term adverse reaction, of which 0.5% of them are considered serious or severe. In addition, the country does not yet have a system for monitoring, alerts, notifications and analysis of information from donors and recipients that would make it possible to identify the causes of the problem for decision-making in an effort to reduce the number of adverse events. This is why we wanted to take advantage of the Blockchain technology through an API REST, based on a centralized architecture, which is responsible for optimizing the processes of hemovigilance by maintaining a constant and unchanging monitoring of information related to the causes that generate adverse events in the transfusion chain.